Affective filter influencing the development of speaking skills in EFL learners - Guale Parrales, Lady Dajely (2022)
This research was conducted to determine the influence of affective filters on the development of young learners' foreign language speaking ability. These filters will allow us to identify how they negatively and positively influence the learning of English as a foreign language, focusing on speaking skills. The design of this research was qualitative, and the instrument was a focus group. The population was focused on 4th grade students in order to know the real situation of affective filters in the development of speaking skills. According to the results of the research, it can be concluded that depending on the affective filter in oral expression students develop certain basic factors that influence the acquisition of a second language; among them, anxiety, motivation, attitude, the interaction between the teacher and the student as well as the influence of parents will decrease or increase the affective filter. Therefore, the affective filter has a great influence on the development of speaking competence, but it can be reduced by the correct application of teaching tactics through games, good relationship with classmates and comfortable classroom environment in the process of developing speaking in young learners.